2021
DOI: 10.7759/cureus.18181
|View full text |Cite
|
Sign up to set email alerts
|

Total Laryngectomy: A Review of Surgical Techniques

Abstract: Since the first total laryngectomy was performed in the late 18th century, several improvements and variations in surgical techniques have been proposed for this procedure. The surgical techniques employed in total laryngectomy have not been comprehensively discussed to date. Thus, the main objective of this article was to address controversial aspects related to this procedure and compare different surgical techniques used for a total laryngectomy procedure from the beginning to the end.Although the managemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 90 publications
0
7
0
Order By: Relevance
“…[4] The upper respiratory tract is disrupted in total laryngectomy patients, and their trachea and lower respiratory tract are directly connected to the environment. [18] Based on this, we hypothesized that patients with total laryngectomy less frequently have SARS-CoV-2 disease; in addition, COVID-19 has a more severe clinical picture in the total laryngectomy patients since the lower respiratory tract and lungs are directly exposed to the virus. In the COVID-19 guideline of the Ministry of Health of the Republic of Türkiye, RT-PCR, which is primarily studied with a naso/oropharyngeal swab sample, is recommended for the diagnosis of SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
“…[4] The upper respiratory tract is disrupted in total laryngectomy patients, and their trachea and lower respiratory tract are directly connected to the environment. [18] Based on this, we hypothesized that patients with total laryngectomy less frequently have SARS-CoV-2 disease; in addition, COVID-19 has a more severe clinical picture in the total laryngectomy patients since the lower respiratory tract and lungs are directly exposed to the virus. In the COVID-19 guideline of the Ministry of Health of the Republic of Türkiye, RT-PCR, which is primarily studied with a naso/oropharyngeal swab sample, is recommended for the diagnosis of SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
“…In Video S1, Supporting Information the long Apron skin incision 10 is performed to provide lateral neck good exposure. Flap is elevated superiorly in the subplatysmal plane, until exposure extends above to the upper border of the hyoid bone and below to the cervical trachea.…”
Section: Video Descriptionmentioning
confidence: 99%
“…Several issues regarding surgical techniques for pharyngeal reconstruction have been studied. For example, recent studies have shown that the use of continuous sutures is associated with lower fistula rates than interrupted sutures in mucosal repair, and nonclosure of the pharyngeal constrictor muscle is not associated with a higher rate of fistula formation [ 2 , 30 ]. However, the relationship between shapes of pharyngeal closure and fistula outcome is not well-established and the study aims to address this.…”
Section: Reviewmentioning
confidence: 99%
“…Previous radiotherapy, T-stage, flap reconstruction, and underlying health conditions such as smoking, anemia, and malnutrition, are known risk factors for post-operative fistula [ 1 ]. Surgical techniques during neopharyngeal reconstruction may affect the occurrence of the fistula, but this has not been thoroughly researched [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation